Kebijakan Peningkatan Kompetensi Sumber Daya Manusia sebagai Pendorong Pertumbuhan Ekonomi Kota Surabaya - Ardiansyah Hendra Lukmana; Allen Pranata Putra (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2025)
The disparity between pace of economic growth and quality of human resources in urban areas such as Surabaya indicates a potential mismatch between policy interventions and actual workforce readiness. Therefore, assessing effectiveness of competency development policies is crucial to ensure sustainable and inclusive economic advancement. This study uses qualitative methods and data collection techniques through in-depth interviews, documentation, and observations of various stakeholders including local governments, business world, and educational institutions. Strategic Human Resource Management (SHRM) and Public Policy Theory are used as analytical frameworks to understand how HR policies are designed, implemented, and the challenges faced in the process. Results of the study show that although government has implemented various job training programs, existing policies still face obstacles in cross-sector coordination, lack of integration with industry needs, and limited program evaluation mechanisms. The business world tends to be less involved in policy formulation, while educational institutions face a gap between the curriculum and skills needed by the job market. To increase the effectiveness of policies, reforms in competency-based training systems are needed, strengthening synergies between the public and private sectors, and incentives for companies that invest in workforce development. The limitation of this study lies in the scope that is still limited to a qualitative perspective and has not measured the impact of the policy quantitatively. Therefore, further research is recommended to use a mixed-method approach to obtain a more comprehensive understanding and compare with other regions. With more strategic and evidence-based policy recommendations, it is hoped that the improvement of human resource competence can further contribute to the competitiveness of the workforce and economic growth in Surabaya.